2019
DOI: 10.1111/jan.14121
|View full text |Cite
|
Sign up to set email alerts
|

Integrative review; identifying the evidence base for policymaking and analysis in health care

Abstract: Aim The aim of this was to identify and synthesize the evidence underpinning the health policymaking process to inform the development of a health‐related policy analysis framework. Design A mixed methods review using “Best Fit” Framework synthesis. Data Sources PUBMED and CINAHL+ databases for English language papers published between March 2013 – March 2017. Review Methods Titles were screened, data abstracted and analysed by two authors at each stage. Findings from included studies were coded against six a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
0
2
0
1
Order By: Relevance
“…The framework also acts as a reminder for the importance of continuous and engaged cooperation and consultation among all players of the policy environment. In fact, previous research demonstrated the value of cooperation and consultation during policy development and throughout the policy cycle as one that leads to better and more innovative policies that truly address the issue [ 34 ]. Finally, the framework can facilitate policymaking as it allows for the identification of numerous policy options that would be generated as the result of consultations and engagements.…”
Section: Discussionmentioning
confidence: 99%
“…The framework also acts as a reminder for the importance of continuous and engaged cooperation and consultation among all players of the policy environment. In fact, previous research demonstrated the value of cooperation and consultation during policy development and throughout the policy cycle as one that leads to better and more innovative policies that truly address the issue [ 34 ]. Finally, the framework can facilitate policymaking as it allows for the identification of numerous policy options that would be generated as the result of consultations and engagements.…”
Section: Discussionmentioning
confidence: 99%
“…Policy analysis aims to understand what is the governments’ focal point, investigate why and how governments issue policies, evaluate the effects of certain policies (Browne et al, 2019 ), and reflect political agenda driven by social concerns or international trends (Kennedy et al, 2019 ). In this study, a bibliometric analysis of a large number of publications on historical policy analysis was carried out to explore the policy problems of concern and the relevant possible options from an evolutionary perspective, and provide a guide for future research.…”
Section: Discussionmentioning
confidence: 99%
“…O foco é o contexto de implementação do PHPN, o conteúdo e a consulta às partes interessadas, que corroboram os resultados sobre a complexidade do processo de formulação de programas e políticas, em face de pressões conflitantes. 78 Pela natureza de seus conteúdos, as recomendações servem de inspiração para uma reflexão a posteriori pelo(a)s leitore(a)s e as contribuições originais desta pesquisa podem servir para a implantação de múltiplas iniciativas relacionadas à prática da advocacy.…”
Section: Advocacy E Violência Obstétricaunclassified